Fosinopril inhibits Ang II-induced VSMC proliferation, phenotype transformation, migration, and oxidative stress through the TGF-β1/Smad signaling pathway - Chen Siqi; Ye Lingxiang (Open Life Sciences)
Fosinopril (FOS) is an angiotensin-converting enzyme inhibitor that can decrease angiotensin II (Ang II) formation, thereby reducing systemic vasoconstriction. This study investigated the impact of FOS on vascular smooth muscle cell (VSMC) phenotypic transformation in hypertension. Experiments using western blotting revealed that FOS inhibits the Ang II-induced downregulation of α-SMA and SM22α and the upregulation of OPN in VSMCs. In addition, CCK8 assays, EdU staining, and Transwell assays demonstrated that FOS reduces Ang II-induced increases in VSMC cell viability, proliferation, migration, and MMP2 and MMP9 expression. Moreover, immunofluorescence and ELISA experiments showed that FOS suppresses Ang II-induced increases in ROS levels, NAD(P)H activity, and NOX2 and NOX4 expression in VSMCs. Western blotting also indicated that FOS inhibits Ang II-induced increases in TGF-β1 and p-Smad2/3 expression in VSMCs. Finally, FOS mitigates Ang II-induced VSMC proliferation, phenotypic transformation, migration, and oxidative stress by inhibiting the TGF-β1/Smad signaling pathway. In conclusion, these results suggest that FOS could be effective in managing vascular diseases, including hypertension.